A separator with high electrolyte wettability, a preparation method thereof and a lithium battery

CN121790683BActive Publication Date: 2026-10-23JIANGXI JINGUANG HIGH TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511959761.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-24
Publication Date
2026-10-23
Estimated Expiration
2045-12-24

AI Technical Summary

Technical Problem

[0003]目前市面上的隔膜主要是聚烯烃类材料,包括聚丙烯膜、聚乙烯膜等,这类膜的优点是价格低廉、力学性能好,但也存在缺陷,如亲电解液性差,润湿性差等,从而导致隔膜的电导率下降,影响锂电池性能

Benefits of technology

1、本申请中所制改性聚乙烯的分子链上具有苯环、环己烷、羧基,相比于普通的聚乙烯,羧基能显著改善聚乙烯的浸润性,从而提高离子电导率,苯环、环己烷热稳定性好,可使隔膜在高温下保持形状不变,降低热收缩率,提升电池安全性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure IMAGE_48E0DE24-EA68-467A-9C0B-FEAD31C44CD5
    Figure IMAGE_48E0DE24-EA68-467A-9C0B-FEAD31C44CD5
  • Figure IMAGE_D0869CB7-304E-4754-B526-4BB37D4FBBBB
    Figure IMAGE_D0869CB7-304E-4754-B526-4BB37D4FBBBB
Patent Text Reader

Abstract

The application discloses a diaphragm with high electrolyte wettability, a preparation method thereof and a lithium battery, and relates to the technical field of battery diaphragm preparation.In the application, a high-temperature-resistant polyether polyol containing a benzene ring is reacted with isophorone diisocyanate and citric acid, and then capped with 1-allyl cyclohexanol to obtain a modifier containing a carboxyl group and a double bond, which is denoted as a double-bond modifier; the double-bond modifier is used for copolymerization with polyethylene to obtain modified polyethylene; the carboxyl group in the double-bond modifier improves the wettability of the polyethylene, and the benzene ring endows the polyethylene with good high-temperature stability; in the application, a hydrophilic flame-retardant coating is coated on the surface of the diaphragm prepared from the modified polyethylene, and the double bond in the coating system is polymerized by ultraviolet light to form a hydrophilic flame-retardant layer; in the case that the wettability of the diaphragm is not affected, the diaphragm is endowed with flame-retardant performance, and the safety of the battery is further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery separator preparation technology, specifically to a separator with high electrolyte wettability, its preparation method, and a lithium battery. Background Technology

[0002] Lithium-ion batteries are one of the main battery choices on the market, boasting advantages such as high energy density, long cycle life, and environmental friendliness. These advantages have led to their widespread use in automobiles, electric vehicles, mobile phones, computers, and other fields. In lithium-ion batteries, the separator is a crucial component, its performance directly affecting the battery's capacity, cycle performance, and safety, thus playing a vital role in the battery's overall performance.

[0003] Currently, the separators on the market are mainly made of polyolefin materials, including polypropylene membranes and polyethylene membranes. The advantages of these membranes are low price and good mechanical properties, but they also have defects, such as poor electrolyte affinity and poor wettability, which leads to a decrease in the conductivity of the separator and affects the performance of lithium batteries.

[0004] Therefore, we propose a separator with high electrolyte wettability, its preparation method, and a lithium battery. By preparing a hydrophilic and high-temperature resistant separator and coating its surface with a hydrophilic flame-retardant coating, we aim to improve the wettability of the separator and thus improve the overall performance of the lithium battery. Summary of the Invention

[0005] The purpose of this invention is to provide a separator with high electrolyte wettability, its preparation method, and a lithium battery, so as to solve the problems raised in the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a separator with high electrolyte wettability, comprising the following processes: Step 1: Mix modified polyethylene, polyvinylpyrrolidone, and white oil, heat and stir to obtain a mixture; Step 2: The mixture is extruded and cooled through a twin-screw extruder to obtain a cast sheet. The cast sheet is then stretched laterally and longitudinally in sequence, and then extracted with an extractant, dried, and heat-set to obtain a modified polyethylene diaphragm. Step 3: Apply a hydrophilic flame-retardant coating to the upper and lower surfaces of the modified polyethylene membrane, and then subject it to ultraviolet irradiation to form a hydrophilic flame-retardant layer, thereby obtaining a membrane with high electrolyte wettability.

[0007] Furthermore, in step 1, the mass ratio of modified polyethylene, polyvinylpyrrolidone, and white oil is 15:(0.8~1.2):(75~85).

[0008] Furthermore, in step 1, the heating and stirring process conditions are: rotation speed 60~70 rpm, temperature 60~65℃, and time 3.0~4.0 min.

[0009] Furthermore, in step 2, the extrusion temperature is 190~200℃; The process conditions for transverse stretching are: stretch ratio 7.5~8.5, stretching temperature 110~120℃; The process conditions for longitudinal stretching are: stretch ratio 1.5~2.5, stretching temperature 120~130℃.

[0010] Furthermore, in step 2, the extractant is prepared by mixing ethyl acetate, n-pentane and cyclohexane in a volume ratio of (1~5):(0.5~1.5):(0.5~1.5).

[0011] Furthermore, in step 2, the drying process conditions are: temperature 50~60℃, time 2~3h; The heat setting process conditions are: temperature 120~140℃, time 5~10min.

[0012] Furthermore, in step 3, the coating thickness of the hydrophilic flame retardant coating is 10~20μm; The process conditions for ultraviolet irradiation are: power 1~3mW / cm 2 Time: 20-30 minutes.

[0013] Furthermore, the preparation process of the modified polyethylene is as follows: Step A: Mix bisphenol A, propylene oxide, and potassium hydroxide, heat to react, and ripen to obtain a high-temperature resistant polyether polyol; Step B: Mix high-temperature resistant polyether polyol, isophorone diisocyanate, and citric acid, heat and react, then add 1-allylcyclohexanol to carry out end-capping reaction to obtain double bond modifier. Step C: Mix dicumyl peroxide, antioxidant, and acetone, then add polyethylene, double bond modifier, and compatibilizer, stir evenly, and melt extrude to obtain modified polyethylene.

[0014] Furthermore, in step A, the mass ratio of bisphenol A, propylene oxide, and potassium hydroxide is 100:(80~85):(0.3~0.8).

[0015] Furthermore, in step A, the process conditions for the heating reaction are: temperature 110~130℃, time 4~6h, and pressure 0.4~0.6MPa; The curing process conditions are: temperature 115~135℃, time 0.5~1.0h.

[0016] Furthermore, in step A, the molecular weight of the high-temperature resistant polyether polyol is 400~700.

[0017] Furthermore, in step B, the mass ratio of high-temperature resistant polyether polyol, isophorone diisocyanate, citric acid, and 1-allylcyclohexanol is 10:(15~20):(1.0~1.2):(1.2~1.6).

[0018] Furthermore, in step B, the process conditions for the heating reaction are: temperature 80~90℃, time 3~4h; The process conditions for the end-capping reaction are: temperature 80~90℃, time 1~2h.

[0019] Furthermore, in step C, the mass ratio of dicumyl peroxide, antioxidant, acetone, polyethylene, double bond modifier, and compatibilizer is (0.5~1.5):(0.04~0.06):10:(90~100):(6~10):(6~12).

[0020] Furthermore, the compatibilizer is maleic anhydride-grafted low-density polyethylene; The antioxidant is one or more of antioxidant 1010, antioxidant 1076, and antioxidant 1035, or a mixture thereof.

[0021] Furthermore, in step C, the temperature of melt extrusion is 180~200℃.

[0022] In the above technical solution, firstly, a high-temperature resistant polyether polyol is obtained by ring-opening bisphenol A with propylene oxide. Then, a hydrophilic carboxyl group is introduced by reacting the isocyanate group of isophorone diisocyanate with the hydroxyl groups of the polyether polyol and citric acid. Next, the isocyanate group is capped by the hydroxyl group of 1-allylcyclohexanol to introduce a double bond. Then, the free radicals generated by heating diisopropylbenzene peroxide attack the hydrogen atoms of polyethylene to generate active free radicals, which promote the addition reaction between the double bond modifier and the polyethylene free radicals to obtain modified polyethylene.

[0023] Furthermore, the hydrophilic flame-retardant coating is prepared by the following process: S1: Under a nitrogen atmosphere, phenyl phosphorus dichloride, aminosiloxane, and anhydrous toluene are mixed, stirred and dispersed evenly, then an acid-binding agent is added, heated and reacted, and filtered to obtain nitrogen-containing phosphorus siloxane. S2: Mix nitrogen-phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent, adjust the pH to 3-4, and perform hydrolysis to obtain double-bonded flame-retardant silica sol. S3: Mix double bond flame retardant silica sol, double bond modifier, ultraviolet photoinitiator, wetting agent, leveling agent, and defoamer, and stir evenly to obtain a hydrophilic flame retardant coating.

[0024] Furthermore, in S1, the molar ratio of phenylphosphine dichloride, aminosiloxane, and acid-binding agent is (1.5~2.5):1:(1~3). The mass ratio of phenylphosphine dichloride to toluene is 1:(60~80).

[0025] Furthermore, the acid-binding agent is triethylamine.

[0026] Furthermore, in S1, the aminosiloxane is one or a mixture of two of 3-aminopropyltriethoxysilane, N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane, and N-aminoethyl-3-aminopropylmethyldimethoxysilane.

[0027] Furthermore, in S1, the process conditions for the heating reaction are: temperature 90~100℃, time 6~8h.

[0028] Furthermore, in S2, the mass ratio of nitrogen-containing phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent is 10:(5~15):(7~15):(100~140).

[0029] Furthermore, in S2, the solvent is a mixture of water and ethanol in a mass ratio of 1:(6~8); In S2, the double-bonded siloxane is one or a mixture of two of vinyltrimethoxysilane and vinyltriisopropoxysilane.

[0030] Furthermore, in S2, the hydrolysis reaction process conditions are: temperature 25~30℃, time 1.0~1.5h.

[0031] Furthermore, in S3, the mass ratio of double bond flame retardant silica sol, double bond modifier, ultraviolet initiator, wetting agent, leveling agent, and defoamer is 100: (4~6): (0.1~0.5): (0.03~0.10): (0.05~0.10): (0.02~0.10).

[0032] Furthermore, in S3, the ultraviolet photoinitiator is initiator 1173, initiator 184, or initiator 2959; The wetting agent is one or a mixture of two of BYK-310 and BYK-358N; The leveling agent is one or a mixture of BYK-348, BYK-380, and BYK-361; The defoamer is one or a mixture of two of BYK-022 and BYK-024.

[0033] The present invention also proposes a lithium battery with a separator having high electrolyte wettability.

[0034] In the above technical solution, aminosiloxane is first used as a nucleophile to attack phenyl phosphorus dichloride and replace the chlorine atom to obtain nitrogen-containing phosphorus siloxane. Then, under acidic conditions, the nitrogen-containing phosphorus siloxane, double-bonded siloxane and tetraethyl orthosilicate alkoxy group are hydrolyzed to generate silanol. The silanols condense to form a silica sol system, which is a double-bonded flame-retardant silica sol. Finally, the double-bonded flame-retardant silica sol, double-bonded modifier, ultraviolet photoinitiator and other additives are mixed to obtain a hydrophilic flame-retardant coating. A hydrophilic flame-retardant coating is applied to the surface of a modified polyethylene membrane. After ultraviolet irradiation, an initiator initiates the polymerization of double bonds, forming a hydrophilic flame-retardant layer on the surface of the modified polyethylene membrane.

[0035] Compared with the prior art, the beneficial effects of the present invention are: 1. The modified polyethylene prepared in this application has benzene rings, cyclohexane, and carboxyl groups on its molecular chain. Compared with ordinary polyethylene, the carboxyl groups can significantly improve the wettability of polyethylene, thereby increasing the ionic conductivity. The benzene rings and cyclohexane have good thermal stability, which can make the separator maintain its shape at high temperature, reduce the thermal shrinkage rate, and improve battery safety.

[0036] 2. In this application, double bond modifiers are mixed with double bond flame retardant silica sol. The polar groups (carboxyl groups) in the double bond modifiers make the coating hydrophilic. At the same time, the three elements of nitrogen, phosphorus and silicon work together to further enhance the flame retardancy of the coating. Detailed Implementation

[0037] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0038] In the following specific implementation; Polyvinylpyrrolidone, model K30, is sourced from Huzhou Shenhua Polymer Materials Co., Ltd. White oil, type 7, kinematic viscosity at 40℃ is 40 cst, sourced from Nantong Dayao Chemical Co., Ltd. The compatibilizer is maleic anhydride-grafted low-density polyethylene, grade 41E710, sourced from Dongguan Shengli New Materials Co., Ltd. The antioxidant is antioxidant 1010; The acid-binding agent is triethylamine; The ultraviolet light initiator is initiator 1173; The wetting agent is BYK-310; The leveling agent is BYK-348; The defoamer is BYK-022; The aminosiloxane is 3-aminopropyltriethoxysilane; The double-bonded siloxane is vinyltrimethoxysilane.

[0039] Example 1: A method for preparing a diaphragm with high electrolyte wettability, comprising the following processes: (1) Preparation of modified polyethylene: Step A: Bisphenol A, propylene oxide, and potassium hydroxide are mixed, heated, and matured to obtain a high-temperature resistant polyether polyol; Step B: The high-temperature resistant polyether polyol, isophorone diisocyanate, and citric acid are mixed, heated, and then 1-allylcyclohexanol is added for end-capping to obtain a double bond modifier; Step C: Dicumyl peroxide, antioxidant, and acetone are mixed, and then polyethylene, the double bond modifier, and compatibilizer are added. The mixture is stirred evenly, melt-extruded, and modified polyethylene is obtained; In Step A, the mass ratio of bisphenol A, propylene oxide, and potassium hydroxide is 100:85:0.8; In Step A, the process conditions for the heating reaction are: temperature 130℃, time... The curing process conditions are: temperature 135℃, time 1.0h; in step B, the mass ratio of high-temperature resistant polyether polyol, isophorone diisocyanate, citric acid, and 1-allylcyclohexanol is 10:20:1.2:1.6; in step B, the heating reaction conditions are: temperature 90℃, time 4h; the end-capping reaction conditions are: temperature 90℃, time 2h; in step C, the mass ratio of dicumyl peroxide, antioxidant, acetone, polyethylene, double bond modifier, and compatibilizer is 1.5:0.06:10:100:10:12; in step C, the melt extrusion temperature is 200℃. (2) Preparation of hydrophilic flame-retardant coatings: S1: Under a nitrogen atmosphere, phenyl phosphorus dichloride, aminosiloxane, and anhydrous toluene are mixed, stirred and dispersed evenly, then an acid-binding agent is added, heated and reacted, and filtered to obtain nitrogen-containing phosphorus siloxane; S2: Nitrogen-containing phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent are mixed, pH is adjusted to 4, and hydrolysis reaction is carried out to obtain double-bonded flame-retardant silica sol; S3: Double-bonded flame-retardant silica sol, double-bonded modifier, ultraviolet photoinitiator, wetting agent, leveling agent, and defoamer are mixed and stirred evenly to obtain a hydrophilic flame-retardant coating; In S1, the molar ratio of phenyl phosphorus dichloride, aminosiloxane, and acid-binding agent is 2.5:1:3; phenyl The mass ratio of phosphorus dichloride to toluene is 1:80; in S1, the heating reaction conditions are: temperature 100℃, time 8h; in S2, the mass ratio of nitrogen-containing phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent is 10:15:15:140; in S2, the solvent is a mixture of water and ethanol in a mass ratio of 1:8; in S2, the hydrolysis reaction conditions are: temperature 30℃, time 1.5h; in S3, the mass ratio of double-bonded flame-retardant silica sol, double-bonded modifier, ultraviolet photoinitiator, wetting agent, leveling agent, and defoamer is 100:6:0.5:0.10:0.10:0.10. (3) Preparation of diaphragms with high electrolyte wettability: Step 1: Mix modified polyethylene, polyvinylpyrrolidone, and white oil, heat and stir to obtain a mixture; Step 2: Extrude the mixture through a twin-screw extruder, cool it to obtain a cast sheet, and then stretch the cast sheet laterally and longitudinally, followed by extraction with an extractant, drying, and heat setting to obtain a modified polyethylene diaphragm; Step 3: Coat the upper and lower surfaces of the modified polyethylene diaphragm with a hydrophilic flame-retardant coating, and irradiate with ultraviolet light to form a hydrophilic flame-retardant layer, obtaining a diaphragm with high electrolyte wettability; In Step 1, the mass ratio of modified polyethylene, polyvinylpyrrolidone, and white oil is 15:1.2:85; In Step 1, the heating and stirring process conditions are: rotation speed 7 0 rpm, 65℃, 4.0 min; in step 2, the extrusion temperature is 200℃; the transverse stretching process conditions are: stretch ratio 8.5, stretching temperature 120℃; the longitudinal stretching process conditions are: stretch ratio 2.5, stretching temperature 130℃; in step 2, the extractant is obtained by compounding ethyl acetate, n-pentane, and cyclohexane in a volume ratio of 5:1.5:1.5; in step 2, the drying process conditions are: temperature 60℃, time 3 h; the heat setting process conditions are: temperature 140℃, time 10 min; in step 3, the coating thickness of the hydrophilic flame retardant coating is 20 μm; the ultraviolet irradiation process conditions are: power 3 mW / cm 2 Time: 30 minutes.

[0040] Example 2: A method for preparing a diaphragm with high electrolyte wettability, comprising the following processes: (1) Preparation of modified polyethylene: Step A: Bisphenol A, propylene oxide, and potassium hydroxide are mixed, heated, and matured to obtain a high-temperature resistant polyether polyol; Step B: The high-temperature resistant polyether polyol, isophorone diisocyanate, and citric acid are mixed, heated, and then 1-allylcyclohexanol is added for end-capping to obtain a double bond modifier; Step C: Dicumyl peroxide, antioxidant, and acetone are mixed, and then polyethylene, the double bond modifier, and compatibilizer are added. The mixture is stirred evenly, melt-extruded, and modified polyethylene is obtained; In Step A, the mass ratio of bisphenol A, propylene oxide, and potassium hydroxide is 100:83:0.5; In Step A, the heating reaction conditions are: temperature 120℃, time... 5h, pressure 0.5MPa; the curing process conditions are: temperature 125℃, time 0.8h; in step B, the mass ratio of high-temperature resistant polyether polyol, isophorone diisocyanate, citric acid, and 1-allylcyclohexanol is 10:18:1.1:1.4; in step B, the heating reaction process conditions are: temperature 85℃, time 3.5h; the end-capping reaction process conditions are: temperature 85℃, time 1.5h; in step C, the mass ratio of dicumyl peroxide, antioxidant, acetone, polyethylene, double bond modifier, and compatibilizer is 1.0:0.05:10:95:8:9; in step C, the melt extrusion temperature is 190℃; (2) Preparation of hydrophilic flame-retardant coatings: S1: Under a nitrogen atmosphere, phenylphosphine dichloride, aminosiloxane, and anhydrous toluene are mixed, stirred and dispersed evenly, then an acid-binding agent is added, heated and reacted, and filtered to obtain nitrogen-containing phosphorus siloxane; S2: Nitrogen-containing phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent are mixed, pH is adjusted to 3, and hydrolysis reaction is carried out to obtain double-bonded flame-retardant silica sol; S3: Double-bonded flame-retardant silica sol, double-bonded modifier, ultraviolet photoinitiator, wetting agent, leveling agent, and defoamer are mixed and stirred evenly to obtain a hydrophilic flame-retardant coating; In S1, the molar ratio of phenylphosphine dichloride, aminosiloxane, and acid-binding agent is 2.0:1:2; benzene The mass ratio of phosphorus dichloride to toluene in S1 is 1:70; the process conditions for the heating reaction in S1 are: temperature 95℃, time 7h; the mass ratio of nitrogen-containing phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent in S2 is 10:10:10:120; the solvent in S2 is a mixture of water and ethanol in a mass ratio of 1:7; the process conditions for the hydrolysis reaction in S2 are: temperature 28℃, time 1.3h; the mass ratio of double-bonded flame-retardant silica sol, double-bonded modifier, ultraviolet photoinitiator, wetting agent, leveling agent, and defoamer in S3 is 100:5:0.3:0.07:0.08:0.06. (3) Preparation of diaphragms with high electrolyte wettability: Step 1: Mix modified polyethylene, polyvinylpyrrolidone, and white oil, heat and stir to obtain a mixture; Step 2: Extrude the mixture through a twin-screw extruder, cool it to obtain a cast sheet, and then stretch the cast sheet laterally and longitudinally. After extraction with an extractant, dry and heat-set to obtain a modified polyethylene diaphragm; Step 3: Coat the upper and lower surfaces of the modified polyethylene diaphragm with a hydrophilic flame-retardant coating, and irradiate with ultraviolet light to form a hydrophilic flame-retardant layer, obtaining a diaphragm with high electrolyte wettability; In Step 1, the mass ratio of modified polyethylene, polyvinylpyrrolidone, and white oil is 15:1.0:80; In Step 1, the heating and stirring process conditions are: rotation speed 65... The extrusion process was carried out at rpm, temperature 63℃, and time 3.5 min; in step 2, the extrusion temperature was 195℃; the transverse stretching process conditions were: stretching ratio 8.0, stretching temperature 115℃; the longitudinal stretching process conditions were: stretching ratio 2.0, stretching temperature 125℃; in step 2, the extractant was prepared by compounding ethyl acetate, n-pentane, and cyclohexane in a volume ratio of 3:1.0:1.0; in step 2, the drying process conditions were: temperature 55℃, time 2.5 h; the heat setting process conditions were: temperature 130℃, time 8 min; in step 3, the coating thickness of the hydrophilic flame retardant coating was 15 μm; the ultraviolet irradiation process conditions were: power 2 mW / cm 2 Time: 25 minutes.

[0041] Example 3: A method for preparing a diaphragm with high electrolyte wettability, comprising the following processes: (1) Preparation of modified polyethylene: Step A: Bisphenol A, propylene oxide, and potassium hydroxide are mixed, heated, and matured to obtain a high-temperature resistant polyether polyol; Step B: The high-temperature resistant polyether polyol, isophorone diisocyanate, and citric acid are mixed, heated, and then 1-allylcyclohexanol is added for end-capping to obtain a double bond modifier; Step C: Dicumyl peroxide, antioxidant, and acetone are mixed, and then polyethylene, the double bond modifier, and compatibilizer are added. The mixture is stirred evenly, melt-extruded, and modified polyethylene is obtained; In Step A, the mass ratio of bisphenol A, propylene oxide, and potassium hydroxide is 100:80:0.3; In Step A, the heating reaction conditions are: temperature 110℃. The curing process conditions are: time 4h, pressure 0.4MPa; temperature 115℃, time 0.5h; in step B, the mass ratio of high-temperature resistant polyether polyol, isophorone diisocyanate, citric acid, and 1-allylcyclohexanol is 10:15:1.0:1.2; in step B, the heating reaction conditions are: temperature 80℃, time 3h; the end-capping reaction conditions are: temperature 80℃, time 1h; in step C, the mass ratio of dicumyl peroxide, antioxidant, acetone, polyethylene, double bond modifier, and compatibilizer is 0.5:0.04:10:90:6:6; in step C, the melt extrusion temperature is 180℃. (2) Preparation of hydrophilic flame-retardant coatings: S1: Under a nitrogen atmosphere, phenyl phosphorus dichloride, aminosiloxane, and anhydrous toluene are mixed, stirred and dispersed evenly, then an acid-binding agent is added, heated and reacted, and filtered to obtain nitrogen-containing phosphorus siloxane; S2: Nitrogen-containing phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent are mixed, pH is adjusted to 4, and hydrolysis reaction is carried out to obtain double-bonded flame-retardant silica sol; S3: Double-bonded flame-retardant silica sol, double-bonded modifier, ultraviolet photoinitiator, wetting agent, leveling agent, and defoamer are mixed and stirred evenly to obtain hydrophilic flame-retardant coating; In S1, the molar ratio of phenyl phosphorus dichloride, aminosiloxane, and acid-binding agent is 1.5:1:1; The mass ratio of phenylphosphine dichloride to toluene is 1:60; in S1, the heating reaction conditions are: temperature 90℃, time 6h; in S2, the mass ratio of nitrogen-containing phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent is 10:5:7:100; in S2, the solvent is a mixture of water and ethanol in a mass ratio of 1:6; in S2, the hydrolysis reaction conditions are: temperature 25℃, time 1.0h; in S3, the mass ratio of double-bonded flame-retardant silica sol, double-bonded modifier, ultraviolet photoinitiator, wetting agent, leveling agent, and defoamer is 100:4:0.1:0.03:0.05:0.02. (3) Preparation of diaphragms with high electrolyte wettability: Step 1: Mix modified polyethylene, polyvinylpyrrolidone, and white oil, heat and stir to obtain a mixture; Step 2: Extrude the mixture through a twin-screw extruder, cool it to obtain a cast sheet, and then perform transverse and longitudinal stretching on the cast sheet. After extraction with an extractant, dry and heat-set to obtain a modified polyethylene diaphragm; Step 3: Coat the upper and lower surfaces of the modified polyethylene diaphragm with a hydrophilic flame-retardant coating, and irradiate with ultraviolet light to form a hydrophilic flame-retardant layer, obtaining a diaphragm with high electrolyte wettability; In Step 1, the mass ratio of modified polyethylene, polyvinylpyrrolidone, and white oil is 15:0.8:75; In Step 1, the heating and stirring process conditions are: rotation speed 6... 0 rpm, 60℃, 3.0 min; in step 2, the extrusion temperature is 190℃; the transverse stretching process conditions are: stretch ratio 7.5, stretching temperature 110℃; the longitudinal stretching process conditions are: stretch ratio 1.5, stretching temperature 120℃; in step 2, the extractant is obtained by compounding ethyl acetate, n-pentane, and cyclohexane in a volume ratio of 1:0.5:0.5; in step 2, the drying process conditions are: temperature 50℃, time 2 h; the heat setting process conditions are: temperature 120℃, time 5 min; in step 3, the coating thickness of the hydrophilic flame retardant coating is 10 μm; the ultraviolet irradiation process conditions are: power 1 mW / cm 2 Time: 20 minutes.

[0042] Comparative Example 1: Compared with Example 1, the high-temperature resistant polyether polyol was replaced with propylene glycol, the mass ratio of propylene glycol to isophorone diisocyanate was set to 1:8, citric acid was not added, and the other conditions remained the same as in Example 1.

[0043] Comparative Example 2: Compared with Example 1, the modified polyethylene diaphragm was not coated with a hydrophilic flame-retardant coating, and all other conditions remained the same as in Example 1.

[0044] Comparative Example 3: Compared with Example 1, the high-temperature resistant polyether polyol was replaced with propylene glycol, the mass ratio of propylene glycol to isophorone diisocyanate was set to 1:8, citric acid was not added, and the surface of the modified polyethylene diaphragm was not coated with a hydrophilic flame retardant coating. All other conditions remained the same as in Example 1.

[0045] Experiment: Ionic conductivity test: The ionic conductivity of the modified polyethylene membrane was tested using the AC impedance method; Tensile strength test: The tensile strength of the modified polyethylene diaphragm was tested using a universal testing instrument; Porosity test: The porosity of the modified polyethylene membrane was determined by the liquid absorption method. Specifically, the modified polyethylene membrane was cut into 10×10cm samples, the weight of the samples was weighed and recorded as m1, and then soaked in n-hexadecane for 1 hour. After that, the samples were taken out, the residual n-hexadecane on the surface was gently wiped off, and the weight was weighed again and recorded as m2. Porosity = ; ρ is the density of n-hexadecane; V is the volume of the sample; Wetting test: The contact angle of the diaphragm is measured using a contact angle meter to characterize the wettability of the diaphragm with high electrolyte wettability; High temperature resistance test: Referring to GB / T 36363-2018, the heat shrinkage rate of the diaphragm is tested to characterize the high temperature resistance of the diaphragm with high electrolyte wettability; Flame retardancy test: Refer to GB / T 2406.2-2009 to test the oxygen index of the diaphragm to characterize the flame retardant performance of the diaphragm with high electrolyte wettability; Based on the data in the table above, the following conclusions can be drawn: Compared with Example 1, the modified polyethylene membrane in Comparative Example 1 showed a decrease in ionic conductivity, porosity, and tensile strength. This is because the absence of citric acid prevents the introduction of carboxyl hydrophilic groups, leading to a decrease in the wettability of the membrane and thus a decrease in ionic conductivity. Furthermore, the absence of benzene rings in propylene glycol results in a decrease in tensile strength. Compared with Example 1, Comparative Example 2 did not coat the modified polyethylene membrane with a hydrophilic flame-retardant coating, which is irrelevant to the performance of the modified polyethylene membrane, and therefore, the change is not significant; Compared with Example 1, the ionic conductivity, porosity and tensile strength of Comparative Example 3 all decreased, indicating that the raw materials and processes for modified polyethylene in this application can promote the comprehensive improvement of the ionic conductivity, porosity and tensile strength of the modified polyethylene diaphragm.

[0046] Based on the data in the table above, the following conclusions can be drawn; Compared with Example 1, Comparative Example 1 replaced the high-temperature resistant polyether polyol with propylene glycol and did not add citric acid. The contact angle of the diaphragm increased and the heat shrinkage rate increased, indicating that the wettability and high-temperature resistance decreased. This is because propylene glycol does not have a high-temperature resistant benzene ring and lacks the polar carboxyl group, thus reducing wettability and thermal stability. Compared with Example 1, the oxygen index of Comparative Example 2 decreased significantly, indicating that the flame retardant performance of the prepared diaphragm decreased. This is because polyethylene film is a flammable material and is not coated with a coating containing nitrogen, phosphorus and silicon, which significantly reduces its flame retardant performance. Compared with Example 1, the performance of Comparative Example 3 decreased significantly, indicating that the selection of raw materials and the setting of process conditions in this application can promote the comprehensive improvement of the wettability, thermal stability and flame retardant performance of the prepared diaphragm.

[0047] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing a diaphragm with high electrolyte wettability, characterized in that: Including the following processes: Step 1: Mix modified polyethylene, polyvinylpyrrolidone, and white oil, heat and stir to obtain a mixture; Step 2: The mixture is extruded and cooled through a twin-screw extruder to obtain a cast sheet. The cast sheet is then stretched laterally and longitudinally in sequence, and then extracted with an extractant, dried, and heat-set to obtain a modified polyethylene diaphragm. Step 3: Apply a hydrophilic flame-retardant coating to the upper and lower surfaces of the modified polyethylene membrane, and irradiate it with ultraviolet light to form a hydrophilic flame-retardant layer, thus obtaining a membrane with high electrolyte wettability. The preparation process of the modified polyethylene is as follows: Step A: Mix bisphenol A, propylene oxide, and potassium hydroxide, heat to react, and ripen to obtain a high-temperature resistant polyether polyol; Step B: Mix high-temperature resistant polyether polyol, isophorone diisocyanate, and citric acid, heat and react, then add 1-allylcyclohexanol to carry out end-capping reaction to obtain double bond modifier. Step C: Mix dicumyl peroxide, antioxidant, and acetone, then add polyethylene, double bond modifier, and compatibilizer, stir evenly, melt extrude, and obtain modified polyethylene; The hydrophilic flame-retardant coating is prepared by the following process: S1: Under a nitrogen atmosphere, phenyl phosphorus dichloride, aminosiloxane, and anhydrous toluene are mixed, stirred and dispersed evenly, then an acid-binding agent is added, heated and reacted, and filtered to obtain nitrogen-containing phosphorus siloxane. S2: Mix nitrogen-phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent, adjust the pH to 3-4, and perform hydrolysis to obtain double-bonded flame-retardant silica sol. S3: Mix double bond flame retardant silica sol, double bond modifier, ultraviolet photoinitiator, wetting agent, leveling agent, and defoamer, and stir evenly to obtain a hydrophilic flame retardant coating.

2. The method for preparing a diaphragm with high electrolyte wettability according to claim 1, characterized in that: In step C, the mass ratio of dicumyl peroxide, antioxidant, acetone, polyethylene, double bond modifier, and compatibilizer is (0.5~1.5):(0.04~0.06): 10:(90~100):(6~10):(6~12)。 3. The method for preparing a diaphragm with high electrolyte wettability according to claim 1, characterized in that: In S1, the molar ratio of phenylphosphine dichloride, aminosiloxane, and acid-binding agent is (1.5~2.5):1:(1~3).

4. The method for preparing a diaphragm with high electrolyte wettability according to claim 1, characterized in that: In S2, the mass ratio of nitrogen-containing phosphorus siloxane, double-bonded siloxane, tetraethyl orthosilicate, and solvent is 10:(5~15):(7~15):(100~140).

5. The method for preparing a diaphragm with high electrolyte wettability according to claim 1, characterized in that: In step 3, the coating thickness of the hydrophilic flame retardant coating is 10~20μm; The process conditions for ultraviolet irradiation are: power 1~3mW / cm2, time 20~30min.

6. The method for preparing a diaphragm with high electrolyte wettability according to claim 1, characterized in that: In step 2, the extractant is prepared by mixing ethyl acetate, n-pentane and cyclohexane in a volume ratio of (1~5):(0.5~1.5):(0.5~1.5).

7. A diaphragm with high electrolyte wettability, characterized in that: The preparation method according to any one of claims 1 to 6 is used.

8. A lithium battery comprising a separator with high electrolyte wettability as described in claim 7.

Citation Information

Patent Citations

  • Preparation method of high-wettability polyolefin diaphragm for lithium ion battery

    CN116454530A

  • Diaphragm with high electrolyte infiltration rate and preparation method thereof

    CN116895907A